CHEMICAL COMPOSITION CHANGE OF SUBSURFACE SNOW IN EAST ANTARCTICA WITH DISTANCE FROM THE COAST - L. P. Golobokova; T. V. Hodzher; Yu. A. Shibaev; V. A. Lipenkov; J.-R. Petit (Лëд и снег, 2015)
The paper presents data on chemical composition of snow in theAntarcticasampled along the first tractor traverse during the 53th Russian Antarctic Expedition from Station Progress (the sea coast) to Station Vostok (1,276 kmfrom Progress). Specific features of horizontal and depth distribution of chemical components in snow revealed differences in conditions of formation of snow cover along the traverse in both spatial and time scales. Chemical composition of snow depends on the sources of admixture inputs onto the surface of the ice sheet (marine, continental and volcanic). The influence of sea factor decreases with the distance from the coast. Calculated factor of element enrichment indicated that some ions in snow cover were of continental origin in the middle of the traverse. Elevated concentrations of sulphate ions were recorded in snow-firn cores at 130–150 cmfrom the surface. They were attributed to signals of the Pinatubo volcano eruption (1991). Accumulation rate of snow was calculated for the traverse sites based on the depth of the Pinatubo layer.